Allergic bronchopulmonary aspergillosis in children. (24th November 2020) - Manti, Sara; Fabio Parisi, Giuseppe; Papale, Maria; Licari, Amelia; Chiappini, Elena; Mulè, Enza; Rotolo, Novella; Leonardi, Salvatore
Abstract: Allergic bronchopulmonary aspergillosis (ABPA) is a pulmonary disease caused by Aspergillus induced hypersensitivity that occurs in immunocompetent but susceptible patients with asthma and/or cystic fibrosis (CF). In children, ABPA remains mostly undiagnosed resulting in one of the most common causes of poorly controlled asthma and highly significant morbidity in children with CF. Currently, no specific diagnostic criteria of ABPA for children are available. Corticosteroids and itraconazole are the mainstays of therapy although there is a lack of randomized clinical trials regarding their usefulness for ABPA in children. Several monoclonal antibodies, such as omalizumab and mepolizumab, may be potential therapies for refractory ABPA in pediatric patients; however, further data are required to clarify the optimal dose and duration of therapy as a routine treatment approach.